2020
DOI: 10.3844/ajbbsp.2020.407.416
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Antimicrobial Collagen Casings with High Mechanical Properties

Abstract: Tea Polyphenols (TP) has received much attention for their excellent antioxidant and antibacterial activities. Some additives (such as sodium alginate and sodium pyrophosphate) have good hydrophobicity which have influence on the mechanical properties of food. The effect of TP on the antibacterial activity of collagen casing was investigated, the effect of addition of TP, sodium pyrophosphate and sodium alginate on mechanical properties including tensile force, tensile strength and elongation at break were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…2A and Fig. 3A, the longitudinal and transverse tensile force increased firstly and then decreased as the concentration of sodium alginate increased, which was consistent with our previous research (Xie et al, 2020). We also found that longitudinal tensile force reached the lowest value and transverse tensile force reached highest value when concentration of TP was 1.5 and 1.99%, respectively ( Fig.…”
Section: Effect Of Independent Variables On Tensile Forcesupporting
confidence: 90%
See 1 more Smart Citation
“…2A and Fig. 3A, the longitudinal and transverse tensile force increased firstly and then decreased as the concentration of sodium alginate increased, which was consistent with our previous research (Xie et al, 2020). We also found that longitudinal tensile force reached the lowest value and transverse tensile force reached highest value when concentration of TP was 1.5 and 1.99%, respectively ( Fig.…”
Section: Effect Of Independent Variables On Tensile Forcesupporting
confidence: 90%
“…In response surface experimental, RSM using BBD was employed to investigate the relationship between three independent variables (X1, concentration of sodium alginate; X2, concentration of sodium pyrophosphate; X3, concentration of TP) that was code at three levels (-1, 0, 1) and six dependent variables (Y1, longitudinal tensile force; Y2, transverse tensile force; Y3, longitudinal tensile strength; Y4, transverse tensile strength; Y5, longitudinal elongation at break; Y6, transverse elongation at break) of collagen casings in this study (Table 1). All the ranges of the parameters in RSM were selected based on the results of single factor experiments according to our previous study (Xie et al, 2020). The concentrations of sodium alginate, sodium pyrophosphate and TP varied from 2.5 to 3.5%, 2.5 to 3.5% and 1.5 to 2.5%, respectively.…”
Section: Response Surface Experimental Designmentioning
confidence: 99%
“…In tests, researchers have demonstrated that the addition of antibacterial tea polyphenols to collagen casings significantly improves the mechanical properties of the casings and increases the antibacterial activity against Escherichia coli, Staphylococcus aureus, Bacillus subtilis and Salmonella [ 22 ]. Collagen can also be modified by crosslinking with other proteins that are thermally stable [ 23 ].…”
Section: Types Of Bio-based Materialsmentioning
confidence: 99%